Molecular Alterations in Metastatic Ovarian Cancer From Gastrointestinal Cancer - Chen, Chao; Ge, Xiaoxu; Zhao, Yamei; Wang, Da; Ling, Limian; Zheng, Shu; Ding, Kefeng; Wang, Jian; Sun, Lifeng (Frontiers in Oncology, 2020)
Most metastatic ovarian cancer (MOC) originates from gastrointestinal cancer (GIC). GIC metastasize to ovary frequently via 3 major routes: hematogenous spread, lymphogenous spread and transcoelomic spread. However, the mechanism of the progression remains unknown and there are few literatures about molecular alteration involved in MOC from GIC. We collected the present evidences and researches on the vital molecules of metastatic pathway and analyzed them systematically with the aim of exploring the mechanism of metastatic pathway of MOC. This review described dominating molecular alteration in the metastatic process from cancer cell detaching away lesion to arrive at ovary, including factors for regulating signaling pathways in epithelial-interstitial transformation, invading and surviving in the circulatory system or abdominal cavity. Besides, the basis of ovary as a distant metastatic site was concerned. We expect this article can help other scholars have new thoughts of the metastatic pathway and generate novel therapeutic targets which will serve as an effective treatment for better outcomes of GIC patient.